Temperature-dependent effects of neonicotinoids on the embryonic development of zebrafish (Danio rerio) - Wang, Yolina Yu Lin; Cai, Yan-Er; Kazmi, Syed Shabi Ul Hassan; Yang, Jing; Wang, Yuwen; Li, Ping; Liu, Wenhua; Wang, Zhen (Frontiers in Marine Science, 2023)
Agricultural use of neonicotinoids is increasing worldwide, and posed threat to the non-target organisms. The existing toxicity data of neonicotinoids that is mainly focused on widely used neonicotinoids, ignores the influence of environmental factors like temperature related to climate changes etc. To fill this data gap, the present study assessed the temperature dependent toxicity of six neonicotinoids at four temperatures. Briefly, fish embryo toxicity test (FET) was performed at following temperatures (20, 23, 28 and 33℃) on zebrafish embryos to evaluate the lethal and sublethal effects of these toxicants. At 28℃ the lethal toxicity (LC50) values for these toxicants were; cycloxaprid 3.36 mg/L, nitenpyram 7.08 mg/L, paichongding 17.2 mg/L, imidaclothiz 738.6 mg/L, dinotefuran 2096 mg/L, thiamethoxam 4293 mg/L, respectively. Among sublethal effects the enzymatic activities changed significantly in neonicotinoids-treatments, revealed the oxidative stress, metabolic disorders, and neurotoxicity. Particularly, the acetylcholinesterase (AChE) inhibition and Glutathione S-transferase (GST) activation showed significant dose-response relationship. However, cycloxaprid, nitenpyram and paichongding were found to be more potent as compared to imidaclothiz and thiamethoxam. The influence of temperature on these neonicotinoids demonstrated an inverted V-shape relationship, in which toxicity decreased with the increase of temperature, and then increased with the increase of temperature after exceeding the optimum temperature. This study provides a reference for multiscale effects and potential mechanisms of neonicotinoids, the temperature-dependent toxicity is of great significance for future toxicity testing and risk assessment of chemicals in the face of global climate changes.